Sensitivity of minimally invasive protocols to monitor changes in endurance performance in elite junior football (soccer) players - Schimpchen, J.; Correia, P. F.; Meyer, T. (International Journal of Sports Physiology and Performance, 2024)
Purpose: Adequate physical fitness is a key requirement for elite footballers. Maximal fitness tests are the standard for evaluating fitness but are often fatiguing and time consuming. This study investigated the ability of various minimally invasive protocols to reflect changes in standard parameters of football players` physical fitness.